2022
DOI: 10.1155/2022/6508289
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of Mechanical Crimping in the Terminal Crimping Process Using a Response Surface Methodology

Abstract: This research aims to optimize the tensile mechanical properties in the terminal crimping process in the terminal 064 series using central composite designs (CCD) of response surface methodology (RSM) on pull force using the Minitab 18 Program. Pull force testing is the mechanical property of the indicator in the crimping process. Three independent variables of the crimp dimensions were studied, including crimp height, crimp depth, and crimp width. The optimum crimp dimensions to sustain a maximum impact pull … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Response surface methodology (RSM) is a test design method proposed by Box et al It is an optimization method that integrates test design and mathematical modeling [22][23][24][25][26][27]. By performing tests on representative local points, the functional relationship between factors and results in the global scope is regressed and fitted, and the optimal level value of each element is obtained.…”
Section: Response Surface Methodology and Its Application In Dance He...mentioning
confidence: 99%
See 1 more Smart Citation
“…Response surface methodology (RSM) is a test design method proposed by Box et al It is an optimization method that integrates test design and mathematical modeling [22][23][24][25][26][27]. By performing tests on representative local points, the functional relationship between factors and results in the global scope is regressed and fitted, and the optimal level value of each element is obtained.…”
Section: Response Surface Methodology and Its Application In Dance He...mentioning
confidence: 99%
“…In recent years, the progress of computer and information technology [18][19][20][21][22][23] has also provided a powerful tool for the dance health and training safety analysis of this study. In order to promote the safety of dance teaching and competition, this study adopts response surface methodology [22] to study the accidental injuries and characteristics in dance teaching and competition, analyzes the causes, and puts forward corresponding safety precautions to reduce the incidence of injuries in safety measures.…”
Section: Introductionmentioning
confidence: 99%
“…However, the tool utilized applies non-uniform pressure to the surface of the terminal during crimping, so crimped terminals often have many defects. Moreover, this tool is controlled by a worker, so achieving uniform-quality crimped terminals is very difficult [2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, the determination of a proper process for achieving high-quality crimped terminals has been intensively studied. Jongwuttanaruk and Thavornwat [3] used response surface methodology optimization of the mechanical crimping process to solve the problem wherein loose wire strands are present. Optimal crimping conditions for the terminal 064 series, which has open wings with cores exposed, were selected; in terms of tensile mechanical properties, a pull-out force of more than 0.07 kN was achieved.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Jongwuttanaruk et al [ 15 ] reported on the use of response surface methodology to optimize the mechanical crimping process. Yu et al [ 16 ] designed an electromagnetic pulse crimping device, which uses a strong pulsed magnetic field to act on the metal workpiece to produce plastic deformation to complete the joint connection.…”
Section: Introductionmentioning
confidence: 99%